The Perceptions and Behavior of Midwives Toward Screening Stimulation, Detection, and Early Intervention of Child Growth and Development in Public Health Center Kudus (Universitas Negeri Semarang, 2020)
Under sixteen percent (26,7 million) of Indonesia children experienced developmental disorders, both fine and gross motorik development, hearing loss, less intelligence and delay. Every 2 out of 1,000 babies experienced motoric development disorders and 3 babies up to 6 babies out of 1,000 have hearing loss and 1 out of 100 children have less intelligence and slowness of speech. Based on data from children in Kudus city, 70,845 who experienced delays in malnutrition were 516 (0.87%) and stunting 20 (0.02%). The implementation of SDIDTK (Screening Stimulation, Detection, and Early Intervention of Child Growth and Development) was carried out by health workers, namely midwives as the spearhead. Research purpose it was to analyze the perceptions and behavior of Midwives toward SDIDTK in Wergu Wetan Public Health Center Kudus. This research used a qualitative method with phenomology approachment. Data collection techniques with in-depth interview. It was found that there were still many midwives who had not yet carried out SDIDTK (Stimulation, Detection, and Early Intervention of Child Growth and Development) according to the guidelines due to lack of time and lack of HR in its implementation. SDIDTK as one of the children’s program that requires the participation of all parties.